Power-limited electric tracing band welding-free production process
By using composite conductive fillers of graphene and carbon nanotubes and adding functional fillers such as antioxidants, the problems of uneven conductivity and insufficient weather resistance of the electrical heat-tracing belt are solved. The mechanical clamping module is used to fix the electrodes, achieving efficient and reliable Electric traction products.
Patent Information
- Application Number
- CN202411698973.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The current electrical heating belts have uneven conductivity, insufficient weather resistance, and unreliable welding connections, which affect the heating efficiency, reliability and service life of the product.
The composite conductive filler of graphene and carbon nanotubes is uniformly dispersed through twin-screw blending technology to form an excellent conductive network. At the same time, antioxidants, ultraviolet absorbers and nano-alumina are added to improve the stability of the material. Use mechanical clamping modules and conductive adhesive fixing electrode modules to avoid welding.
It significantly improves the conductive properties and mechanical strength of the material, extends the service life of the product in harsh environments, and ensures the stability and reliability of the electrical heat ties.
Smart Images

Figure CN119485824A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric heating tapes, and in particular to a welding-free production process for power-limited electric heating tapes. Background Art
[0002] Electric heating tape is a widely used electric heating product, mainly used in the fields of industrial pipeline insulation, antifreeze and temperature maintenance of chemical storage tanks. Traditional electric heating tape usually connects the electrode to the heating core by welding, and relies on multi-step processing to achieve the superposition of the insulation layer, shielding layer and outer sheath. However, the existing technology has the following major shortcomings.
[0003] The heating core of existing electric heating cables is mostly made of a single conductive filler, which has an uneven conductive network and low electronic conduction efficiency, resulting in high resistivity and unstable power output, affecting the overall heating efficiency and reliability of the electric heating cables. Electric heating cables are usually exposed to high humidity, high temperature and strong ultraviolet light environments. The aging rate of existing materials is relatively fast, and the insulation layer and outer sheath are prone to failure in long-term use, which seriously affects the service life of the product. Traditional welding processes require high-temperature treatment, which is easy to cause thermal damage to the heating core material, thereby reducing the mechanical strength and service life of the electric heating cables. In addition, welding points are easily affected by external vibrations and mechanical stress, which may cause unstable connections. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a welding-free production process for power-limited electric heating tapes, which solves the problems of uneven conductivity, insufficient weather resistance and unreliable connection in the production of electric heating tapes.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a power-limited electric heating tape welding-free production process, comprising the following steps
[0006] S1. Prepare the heating core material: uniformly coat the base material and the conductive filler on the metal wire through a melt blending and extrusion process;
[0007] S2, through the multi-layer co-extrusion equipment, the insulation layer, the shielding layer and the outer sheath are sequentially extruded on the outer surface of the heating core;
[0008] S3, cutting the electric heating cable to a fixed length by laser cutting equipment, and sealing the end by a combined injection process of silicone rubber and hot melt adhesive;
[0009] S4, using mechanical clamping module combined with conductive glue coating to fix the electrode module to both ends of the heating core;
[0010] S5. Conduct power-on test, insulation strength test and appearance defect test on the finished products and complete packaging.
[0011] Preferably, in step S1, the conductive filler is 60%-70% graphene and 30%-40% carbon nanotubes.
[0012] Preferably, in step S1, the substrate is cross-linked polyethylene, and 0.3%-0.5% antioxidant, 0.2%-0.4% ultraviolet absorber and 1%-3% nano-alumina are added.
[0013] Preferably, the step S1 specifically includes the following steps:
[0014] S1.1, stirring 60%-70% of graphene and 30%-40% of carbon nanotubes at high speed for 5 minutes-30 minutes, and pre-treating by ultrasonic dispersion, and dispersing for 10 minutes-60 minutes;
[0015] S1.2, adding 0.3%-0.5% antioxidant, 0.2%-0.4% ultraviolet absorber and 1%-3% nano-alumina into cross-linked polyethylene and stirring;
[0016] S1.3, the conductive filler and the substrate are melt-blended in a twin-screw extruder at a temperature range of 200°C-250°C, and coated on the metal wire with a coating thickness of 0.5mm-0.9mm;
[0017] S1.4. After extrusion, the temperature is lowered in a cooling water tank and cross-linked and cured by electron beam irradiation.
[0018] Preferably, the step S2 specifically includes the following steps:
[0019] S2.1. Use the inner layer die to heat the modified fluorinated polymer (PFA) material to 280°C-320°C, and extrude it evenly to the outer surface of the heating core through the annular die to form an insulating layer with a thickness of 0.7-1.2 mm;
[0020] S2.2. Use automatic winding equipment to wind the tinned copper braided mesh around the outside of the insulation layer in a constant tension mode to ensure that the coverage density reaches 90%-95%;
[0021] S2.3, using an outer layer die head, extrude the thermoplastic polyurethane material at a temperature of 190°C-220°C, and coat the shielding layer to form an outer sheath with a thickness controlled at 1.0-1.5mm;
[0022] S2.4. The extruded multilayer structure is cooled by a cooling section that combines water cooling and air cooling. The length of the cooling section is 3-5 meters to ensure that the multilayer structure is firmly adhered and free of bubbles.
[0023] Preferably, in step S3, a laser device with a power of 8W-12W is used, the cutting speed is 8mm / s-12mm / s, and the end surface after cutting is micro-polished, and the roughness is controlled at Ra0.6μm-1.0μm.
[0024] Preferably, the glue injection process in step S3 specifically includes the following steps:
[0025] S3.1. Inject the silicone rubber into the gap between the heating core and the insulating layer;
[0026] S3.2, inject hot melt adhesive to cover the outer sheath surface, the thickness of the injection is 2mm-5mm;
[0027] S3.3. After sealing, cure in an environment of 50℃-70℃ for 10 hours to 15 hours.
[0028] Preferably, the clamping module in step S4 is an elastic clamping structure made of beryllium copper alloy, and the contact surface of the clamping module is coated with conductive glue.
[0029] Preferably, the conductive adhesive comprises 60%-80% of nano-silver particles, 10%-20% of conductive carbon fibers and 5%-15% of a binder.
[0030] Preferably, the step S5 specifically includes the following steps:
[0031] S5.1. Power on and test the power output of the heating element;
[0032] S5.2, insulation strength test, through 40kV-60kV high voltage test insulation layer breakdown voltage;
[0033] S5.3. Appearance inspection: defects on the outer sheath surface are detected by machine vision system.
[0034] The present invention provides a welding-free production process for power-limited electric heating cables. It has the following beneficial effects:
[0035] 1. The present invention adopts composite conductive fillers of graphene and carbon nanotubes, and evenly disperses them through optimized twin-screw blending technology to form a conductive network structure with excellent continuity. This design significantly improves the conductivity of the material, makes the power output more uniform, avoids local overheating or overcooling, and ensures the stability of the product during long-term operation.
[0036] 2. The present invention effectively improves the stability of the material in high temperature, high humidity and strong ultraviolet light environments by adding antioxidants, ultraviolet absorbers and nano-alumina. The optimized material shows a lower aging rate, prolongs the service life of the electric heating cable in harsh environments, and is particularly suitable for outdoor high-intensity working conditions.
[0037] 3. The present invention not only improves the strength of the substrate, but also significantly enhances the material's tensile strength and crack propagation resistance through the synergistic effect of nano-alumina, graphene and carbon nanotubes. The optimized material can maintain structural integrity in a complex mechanical environment, is not easy to break or deform, and provides reliable protection for the long-term use of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings of the present invention specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Please refer to the attached Figure 1 The embodiment of the present invention provides a welding-free production process for power-limited electric heating tape, comprising the following steps:
[0041] S1. Prepare the heating core material: uniformly coat the base material and the conductive filler on the metal wire through a melt blending and extrusion process;
[0042] S2, through the multi-layer co-extrusion equipment, the insulation layer, the shielding layer and the outer sheath are sequentially extruded on the outer surface of the heating core;
[0043] S3, cutting the electric heating cable to a fixed length by laser cutting equipment, and sealing the end by a combined injection process of silicone rubber and hot melt adhesive;
[0044] S4, using mechanical clamping module combined with conductive glue coating to fix the electrode module to both ends of the heating core;
[0045] S5. Conduct power-on test, insulation strength test and appearance defect test on the finished products and complete packaging.
[0046] Specific;
[0047] preparing heating core materials;
[0048] Material ratio:
[0049] Base material: cross-linked polyethylene, accounting for 90%-93% by mass;
[0050] Conductive filler:
[0051] Graphene: 60%-70% by mass;
[0052] Carbon nanotubes: 30%-40% by mass;
[0053] additive:
[0054] Antioxidants: 0.3%-0.5%;
[0055] UV absorber: 0.2%-0.4%;
[0056] Nano-alumina: 1%-3%;
[0057] Steps:
[0058] The graphene and the carbon nanotubes are mixed in proportion and pretreated by high-speed stirring for 5 minutes to 30 minutes and ultrasonic dispersion for 10 minutes to 60 minutes.
[0059] Mix 0.3%-0.5% antioxidant, 0.2%-0.4% ultraviolet absorber and 1%-3% nano-alumina with cross-linked polyethylene, and stir thoroughly in a stirring device;
[0060] The pretreated conductive filler is mixed with the substrate and melt-blended in a twin-screw extruder at a temperature of 200° C. to 250° C. to form a conductive polymer;
[0061] The conductive polymer is evenly coated on the metal wire through a circular die extrusion device to form a heating layer with a coating thickness of 0.5mm-0.9mm.
[0062] The multi-layer structure is formed by multi-layer co-extrusion equipment.
[0063] Using the inner layer die head, the modified fluorinated polymer (PFA) material is heated to 280°C-320°C, and evenly extruded to the outer surface of the heating core through the annular die to form an insulating layer with a thickness of 0.7-1.2mm;
[0064] The tinned copper braid is wound around the insulation layer in a constant tension mode using an automatic winding device to ensure a coverage density of 90%-95%;
[0065] Using an outer layer die, the thermoplastic polyurethane material is extruded at a temperature of 190°C-220°C, and the shielding layer is coated to form an outer sheath with a thickness controlled at 1.0-1.5mm;
[0066] The extruded multilayer structure is cooled by a cooling section that combines water cooling and air cooling. The cooling section is 3-5 meters long to ensure that the multilayer structure is firmly adhered and free of bubbles.
[0067] Multi-layer co-extrusion technology realizes one-time molding, improves process efficiency, and avoids inter-layer detachment. The insulation layer and outer sheath provide excellent electrical and mechanical protection, ensuring the long-term stability of the electric heating cable in complex environments.
[0068] Use 8W-12W laser equipment, the cutting speed is 8mm / s-12mm / s, and the end surface after cutting is micro-polished, and the roughness is controlled at Ra0.6μm-1.0μm;
[0069] Laser cutting ensures the smoothness of the cut end surface, improves the sealing performance of the electric heating cable, and the multi-layer sealing structure prevents moisture and corrosive substances from entering the interior, ensuring the reliability of the product in high humidity and corrosive environments;
[0070] Inject silicone rubber into the gap between the heating core and the insulating layer;
[0071] Inject hot melt adhesive to cover the outer sheath surface, the thickness of the injection is 2mm-5mm;
[0072] After sealing, cure in an environment of 50℃-70℃ for 10-15 hours;
[0073] Silicone rubber is injected into the gap between the insulation layer and the heating core to provide flexible filling and sealing functions. Hot melt adhesive covers the outer sheath to enhance waterproof and anti-corrosion properties. Multi-layer seals are cured in a constant temperature environment to ensure a firm structure;
[0074] Coat the contact surface of the card-jointed module with conductive glue and fix it to both ends of the heating core. Quickly cure it at 120°C for 5 minutes to form a stable electrical connection.
[0075] The soldering-free technology avoids the thermal damage caused by traditional soldering and improves the reliability of electrode connection.
[0076] Apply working voltage and monitor the power output of the heating core in real time to ensure that the power deviation is controlled within ±3%;
[0077] Insulation strength test, through 40kV-60kV high voltage test insulation layer breakdown voltage appearance test;
[0078] Appearance inspection: detect defects on the surface of the outer sheath through a machine vision system.
[0079] The power-on test ensures the performance consistency and power stability of the product, and the high-voltage insulation test verifies the reliability of the insulation layer, ensuring the safety of the product in a high-voltage working environment.
[0080] Embodiment 1;
[0081] Implementation steps:
[0082] Material preparation:
[0083] Base material: cross-linked polyethylene (XLPE), accounting for 70% by weight;
[0084] Conductive filler: graphene 60%, multi-walled carbon nanotubes 40%;
[0085] Functional fillers: antioxidant 0.4%, ultraviolet absorber 0.3%, nano alumina 2%.
[0086] Process flow:
[0087] Graphene and carbon nanotubes were mixed in a ratio of 6:4 and processed using a ball mill at 300 rpm for 6 hours;
[0088] The ball-milled mixture was dispersed by ultrasonic dispersion equipment for 40 minutes;
[0089] In a twin-screw extruder, the conductive filler is blended with the base material at a temperature of 225°C;
[0090] Use a ring die to extrude and coat the surface of the metal wire to form a heating core with a thickness of 0.6mm;
[0091] The extruded heating core material is cooled in a cooling water tank and then cross-linked and cured by electron beam irradiation;
[0092] Result analysis:
[0093] The heating core material has good conductivity and the resistivity is 0.3Ω.cm;
[0094] High mechanical strength, tensile strength is 20.5MPa;
[0095] The power output uniformity is good, and the deviation is controlled within ±3%
[0096] Summarize:
[0097] In this embodiment, the composition and process parameters are within the recommended range, and the heating core material with the best performance is obtained. Its conductivity, mechanical strength and power uniformity are better than traditional technical solutions, providing a benchmark for subsequent comparative experiments.
[0098] Embodiment 2;
[0099] Implementation steps:
[0100] Material preparation:
[0101] Base material: ordinary polyethylene (PE), accounting for 80% by mass;
[0102] Conductive filler: graphene 50%, multi-walled carbon nanotubes 30%;
[0103] Functional fillers: antioxidant 0.2%, ultraviolet absorber 0.2%, nano alumina 0.8%.
[0104] Process flow:
[0105] Graphene and carbon nanotubes were mixed in a ratio of 5:3 and processed using a ball mill at 200 rpm for 4 h;
[0106] The mixture was dispersed by ultrasonic dispersion equipment for 20 minutes;
[0107] In a twin-screw extruder, the conductive filler is blended with the base material at a temperature of 180°C;
[0108] The extrusion thickness was controlled at 0.5 mm, and the radiation curing process was not used, and it was directly cooled naturally.
[0109] Result analysis:
[0110] The material has poor conductivity, with a resistivity of 0.8Ω.cm;
[0111] The mechanical strength is low, with a tensile strength of 16.8MPa;
[0112] The power output uniformity is poor, with deviations as high as ±8%.
[0113] Summarize:
[0114] In this embodiment, the material properties are significantly reduced because the composition and process parameters are lower than the recommended range, especially the insufficient conductive filler and the imperfect cooling process, which directly affect the conductivity and mechanical strength.
[0115] Embodiment 3:
[0116] Implementation steps:
[0117] Material preparation:
[0118] Base material: cross-linked polyethylene (XLPE), accounting for 60% by mass;
[0119] Conductive filler: graphene 80%, multi-walled carbon nanotubes 50%;
[0120] Functional fillers: antioxidant 0.6%, ultraviolet absorber 0.5%, nano alumina 4%.
[0121] Process flow:
[0122] Graphene and carbon nanotubes were mixed in a ratio of 8:5 and processed using a ball mill at 400 rpm for 8 h;
[0123] The ultrasonic dispersion time was extended to 60 minutes;
[0124] In a twin-screw extruder, the conductive filler is blended with the base material at a temperature of 270°C;
[0125] The extrusion thickness was controlled to 0.8 mm, and after cooling, a 25 Mrad electron beam was used for cross-linking and curing.
[0126] Result analysis:
[0127] The conductivity is significantly improved, and the resistivity is 0.2Ω.cm;
[0128] The mechanical strength is further enhanced, with a tensile strength of 22.5MPa;
[0129] The power output uniformity is excellent, and the deviation is controlled within ±2%.
[0130] Summarize:
[0131] Although the performance is significantly improved, the cost of materials in this embodiment is increased due to the excessively high proportion of conductive fillers and functional fillers, and the complexity of the process is increased, so the economic efficiency is limited to a certain extent.
[0132] Comparative experiment;
[0133] Comparative Example 1:
[0134] Design ideas
[0135] Innovative ingredient 1: Graphene and carbon nanotubes are used as composite conductive fillers to significantly improve the conductivity, mechanical strength and power output uniformity of the heating core material.
[0136] Existing technical solution: Using only a single conductive filler (such as conductive carbon black) as a conductive material cannot form an efficient conductive network
[0137] Comparison plan
[0138] Comparative Example 1:
[0139] Conductive filler: single conductive carbon black;
[0140] Base material: ordinary polyethylene (PE);
[0141] Functional fillers: No antioxidants and UV absorbers added.
[0142] Embodiment 1:
[0143] Conductive filler: graphene 60%, carbon nanotubes 40%;
[0144] Base material: cross-linked polyethylene (XLPE);
[0145] Functional fillers: antioxidant 0.4%, UV absorber 0.3%, nano-alumina 2%
[0146] Comparison of experimental results.
[0147] Test items;
[0148] Electrical conductivity;
[0149] Power uniformity;
[0150] Weather resistance;
[0151] Mechanical strength.
[0152] Comparison of experimental results:
[0153] Test items Comparative Example 1 Example 1 Weather resistance (aging rate, %) 5.5 1.2 Resistivity (Ω·cm) 1.5 0.3 Tensile strength(MPa) 12.3 20.5 Power uniformity deviation (%) ±10 ±3
[0154] The prior art solutions lacking graphene and carbon nanotubes have poor performance in terms of electrical conductivity, power output uniformity and mechanical strength. In contrast, the present invention significantly improves the comprehensive performance of the material through the use of composite conductive fillers.
[0155] Comparative Example 2:
[0156] Comparative Example 2:
[0157] Conductive filler: graphene 60%, carbon nanotubes 40%;
[0158] Functional fillers: No antioxidants, UV absorbers and nano-alumina added.
[0159] Embodiment 1:
[0160] Functional fillers: antioxidant 0.4%, UV absorber 0.3%, nano-alumina 2%
[0161] Comparison of experimental results;
[0162]
[0163] The existing technical solutions without adding functional fillers are obviously insufficient in terms of weather resistance, high temperature stability and dielectric strength. The present invention enhances the environmental adaptability and insulation performance of the material by adding functional fillers, and is particularly suitable for application in harsh environments with high temperature and high humidity.
[0164] Comparative Example 3:
[0165] Comparative Example 3:
[0166] No twin-screw compounding was used, only single-screw extrusion was used;
[0167] Molding process, temperature 300℃;
[0168] No electron beam irradiation curing, direct natural cooling.
[0169] Embodiment 1:
[0170] Use twin screw blending, temperature 225℃;
[0171] Extrusion using a ring die;
[0172] Crosslinking and curing by electron beam irradiation (20 Mrad)
[0173] Comparison of experimental results:
[0174] Test items Comparative Example 2 Example 1 Conductive filler distribution uniformity Poor excellent Finished product thickness uniformity deviation (mm) ±0.2 ±0.05 Bubble generation rate after cooling (%) 15 1.5 Tensile strength(MPa) 15.2 20.5 Power uniformity deviation (%) ±8 ±3
[0175] The prior art process does not use twin-screw blending and radiation curing, resulting in poor material uniformity, high bubble generation rate, large power deviation, and low consistency of finished products. The present invention optimizes the preparation process and significantly improves the mechanical properties and power uniformity of the finished product.
[0176] Experimental data table
[0177] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Weather resistance (aging rate, %) 1.2 3.8 0.8 5.5 3.5 4.2 Resistivity (Ω·cm) 0.3 0.8 0.2 1.5 0.6 0.9 Tensile strength(MPa) 20.5 16.8 22.5 12.3 16.5 15.2 Power uniformity deviation (%) ±3 ±8 ±2 ±10 ±6 ±8 Dielectric strength (kV / mm) 50 30 55 20 25 35 Bubble generation rate after cooling (% 1.5 10 1.0 15 12 15
[0178] Weather resistance (aging rate) analysis;
[0179] Advantages of the present invention:
[0180] The addition of antioxidants and ultraviolet absorbers in the present invention significantly improves the resistance of the material to ultraviolet rays and oxidative environments.
[0181] The use of nano-alumina as filler enhances the structural stability of the substrate, making it less prone to degradation under high humidity and high temperature conditions
[0182] Resistivity analysis;
[0183] Advantages of the present invention:
[0184] Graphene (60%-80%) and carbon nanotubes (40%-50%) are used to form a uniform conductive network, providing a stable electron migration channel and effectively reducing the resistivity.
[0185] In Example 3, due to the higher ratio of graphene and carbon nanotubes, the conductive path is more dense, so the resistivity is further reduced to 0.2Ω·cm
[0186] Tensile strength analysis;
[0187] Advantages of the present invention:
[0188] The addition of nano-alumina (2%-4%) enhances the mechanical strength of the substrate;
[0189] The composite filler of graphene and carbon nanotubes forms an effective stress conduction network, which improves the overall tensile properties of the material.
[0190] Power uniformity deviation analysis;
[0191] Advantages of the Invention
[0192] Graphene and carbon nanotubes are evenly dispersed through twin-screw blending technology, so that the conductive filler is evenly distributed in the substrate, and the power output stability is significantly improved.
[0193] Summarize;
[0194] The synergistic effect of graphene and carbon nanotubes significantly enhances the conductivity and mechanical strength, antioxidants and UV absorbers effectively improve weather resistance and service life, twin-screw blending technology makes the filler distribution uniform, electron beam radiation curing improves structural stability and significantly reduces power deviation and bubble defect rate.
[0195] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A welding-free production process for power-limited electric heating cables, characterized in that: The following steps are included S1. Prepare the heating core material: uniformly coat the base material and the conductive filler on the metal wire through a melt blending and extrusion process; S2, through the multi-layer co-extrusion equipment, the insulation layer, the shielding layer and the outer sheath are sequentially extruded on the outer surface of the heating core; S3, cutting the electric heating cable to a fixed length by laser cutting equipment, and sealing the end by a combined injection process of silicone rubber and hot melt adhesive; S4, using mechanical clamping module combined with conductive glue coating to fix the electrode module to both ends of the heating core; S5. Conduct power-on test, insulation strength test and appearance defect test on the finished products and complete packaging.
2. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: In step S1, the conductive filler is 60%-70% of graphene and 30%-40% of carbon nanotubes.
3. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: In step S1, the substrate is cross-linked polyethylene, and 0.3%-0.5% of antioxidant, 0.2%-0.4% of ultraviolet absorber and 1%-3% of nano-aluminum oxide are added.
4. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: The step S1 specifically includes the following steps: S1.1, stirring 60%-70% of graphene and 30%-40% of carbon nanotubes at high speed for 5 minutes-30 minutes, and pre-treating by ultrasonic dispersion, and dispersing for 10 minutes-60 minutes; S1.2, adding 0.3%-0.5% antioxidant, 0.2%-0.4% ultraviolet absorber and 1%-3% nano-alumina into cross-linked polyethylene and stirring; S1.3, the conductive filler and the substrate are melt-blended in a twin-screw extruder at a temperature range of 200°C-250°C, and coated on the metal wire with a coating thickness of 0.5mm-0.9mm; S1.
4. After extrusion, the temperature is lowered in a cooling water tank and cross-linked and cured by electron beam irradiation.
5. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: The step S2 specifically includes the following steps: S2.
1. Use the inner layer die to heat the modified fluorinated polymer (PFA) material to 280°C-320°C, and extrude it evenly to the outer surface of the heating core through the annular die to form an insulating layer with a thickness of 0.7-1.2 mm; S2.
2. Use automatic winding equipment to wind the tinned copper braided mesh around the outside of the insulation layer in a constant tension mode to ensure that the coverage density reaches 90%-95%; S2.3, using an outer layer die head, extrude the thermoplastic polyurethane material at a temperature of 190°C-220°C, and coat the shielding layer to form an outer sheath with a thickness controlled at 1.0-1.5mm; S2.
4. The extruded multilayer structure is cooled by a cooling section that combines water cooling and air cooling. The length of the cooling section is 3-5 meters to ensure that the multilayer structure is firmly adhered and free of bubbles.
6. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: In the step S3, a laser device with a power of 8W-12W is used, the cutting speed is 8mm / s-12mm / s, and the end surface after cutting is micro-polished, and the roughness is controlled at Ra0.6μm-1.0μm.
7. A welding-free production process for power-limited electric heating cables according to claim 1, characterized in that: The glue injection process in step S3 specifically includes the following steps: S3.
1. Inject the silicone rubber into the gap between the heating core and the insulating layer; S3.2, inject hot melt adhesive to cover the outer sheath surface, the thickness of the injection is 2mm-5mm; S3.
3. After sealing, cure in an environment of 50℃-70℃ for 10 hours to 15 hours.
8. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: In the step S4, the clamping module is an elastic clamping structure made of beryllium copper alloy, and the contact surface of the clamping module is coated with conductive glue.
9. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: The conductive adhesive comprises 60%-80% of nano silver particles, 10%-20% of conductive carbon fibers and 5%-15% of a binder.
10. A welding-free production process for power-limited electric heating tape according to claim 1, characterized in that: The step S5 specifically includes the following steps: S5.
1. Power on and test the power output of the heating element; S5.2, insulation strength test, through 40kV-60kV high voltage test insulation layer breakdown voltage; S5.
3. Appearance inspection: inspect the defects on the surface of the outer sheath through a machine vision system.
Citation Information
Patent Citations
Flame-retardant weather-resistant PTC cable material and preparation method
CN106336646A
Manufacturing method of heat tracing tape with extruded insulating layer
CN108040381A
Self-temperature-limiting electric tracing band with positive temperature coefficient and preparation method of self-temperature-limiting electric tracing band
CN114786282A
Electric heating wire with intelligent temperature control function and heating die assembly prepared by using electric heating wire
CN116489838A
Cited By
Direct-current low-power-consumption nanoscale semiconductor electric heat tracing diaphragm
CN119743858A